WOMENS’ BELIEFS AND PRACTICES REGARDING FOOD RESTRICTIONS DURING PREGNANCY AND LACTATION: A HOSPITAL BASED STUDY - Ali, Niloufer Sultan; Azam, Syed Iqbal; Noor, Rahat (Journal of Ayub Medical College Abbottabad, 2004)
Background: Maternal diet is an important determinant of outcomes of pregnancy. Malnutrition during pregnancy and its consequences maximally affect the health and long-term outcomes of the population. Low birth weight accounts for almost 30% of all births; with maternal malnutrition as a dominant risk factor. This study aims to investigate the existing beliefs and practices regarding food restrictions during pregnancy and lactation and also to assess whether there is any relationship with education level of the respondent and their beliefs and practices. Methods: A cross-sectional survey was conducted at Community Health Center (CHC) of The Aga Khan University Hospital, Karachi from July- September 2000. Four hundred adult female respondents, who came to the outpatient services as a patient or as an attendant, were interviewed after taking verbal consent. A self administered pre-coded and pre-tested questionnaire was filled by the respondent. Results: More than three fourths of respondents were literate. Twelve percent believed in restricting some food item during pregnancy and about 25% believed the same during lactation. No statistically significant association was found between belief about food restriction during pregnancy or during lactation and education level of the respondent. Conclusion: Undue food restrictions during pregnancy and lactation do exist in our culture. To assess the true picture we need to conduct larger studies in the community. The information obtained from the studies will help us in addressing these issues for improvement of nutritional knowledge and dietary practices and to avoid undue food restrictions. Key Words: Food habits; Beliefs; Women’s health; Pregnancy; Lactation.